PERAN MANAJER DALAM PENGELOLAAN RISIKO EKONOMI DI PERUSAHAAN MULTINASIONAL - Amril, Amril; Asriyana, Asriyana; Randy, Muh. Fuad (Bisnis-Net, 2024)
This research examines the critical role managers play in managing economic risk within multinational banking institutions, focusing on how these leaders navigate the complexities of global economic uncertainty. With fluctuating currency exchange rates, diverse regulatory standards, and geopolitical instability, multinational banks face unique challenges that require managers to adopt proactive and adaptive risk management strategies. This study specifically analyzes the most common types of economic risks occurring in multinational banking and explores the decision-making processes, tools, and collaborative approaches managers use to mitigate these risks. Through a qualitative approach, including in-depth interviews with managers across different regions and levels, the study identifies key strategies and technological innovations such as real-time data analysis and predictive modeling that support effective risk management. In addition, the study highlights the role of cross-region communication in maintaining consistency in risk and compliance protocols across borders. This study contributes to a deeper understanding of the managerial skills and resources required to effectively manage economic risk, offering insights that can help multinational banks strengthen their resilience and competitive advantage in an increasingly volatile economic landscape.